What information do general practitioners want about accident and emergency patients? - Wass, A R (1996)
OBJECTIVES: To establish what information general practitioners (GPs) want about their patients who attend accident and emergency (A&E) departments and the GPs' preferences for the type of communication and method of delivery. METHODS: Analysis of questionnaire sent to all 350 GPs in the catchment area of one A&E department. RESULTS: 219 completed questionnaires (63%) were returned. GPs requested information about most new attendances at A&E, but only 50% of GPs wanted details of every new A&E patient. Most GPs preferred a small computer generated letter or sticky label which included details of investigation results, diagnosis, treatment, and follow up arrangements. 47% of GPs requested delivery of letters by the pathology specimen service, but 25% preferred hand delivery by the patient or a relative. Individual GPs often had widely different preferences, especially about the type of communication and method of delivery. Most GPs would value a monthly list of all their patients who have attended A&E. CONCLUSIONS: GPs need prompt and appropriate information about their patients who attend A&E. A computerised records system should be arranged so that relevant information can be produced easily and quickly in a format suitable for filing in GP records. Good communications with GPs would improve the continuity of care for A&E patients.